Vitanolídeos antiproliferativos e anti-Inflamatórios isolados das folhas de Athenaea velutina (Sendtn.) D’Arcy – Solanaceae - Rocha, Késya Amanda Dantas (2023)
Withanolides, steroidal lactones derived from ergostane, are a class of secondary metabolites with important potential pharmacological, particularly against cancer and autoimmune, inflammatory, and neurogenerative diseases. The occurrence of this class of compounds is common in plants of the subfamily Solanoideae (Solanaceaee). The chemical investigation from leave extract of Athenaea velutina resulted in the isolation of fourteen unreported withanolides, including three withajardins and four known withanolides: 27-dehydroxywithaferin A, 2,3-dihydro-27-dehydroxywithaferin A, tuboanesigenin, and withaferin A. The compounds isolation and purification were performed by chromatographic fractionation on sílica gel and high-performance liquid chromatography (HPLC). The compound structures were determined by spectroscopic methods such as IR and NMR (1D and 2D), and mass spectrometry. The absolute configuration was determined by X-ray diffraction and circular dichroism analyses. The antiproliferative properties of the withanolides were evaluated against four human cancer cell lines: SNB-19 (glioblastoma), PC-3 (prostate), HCT-116 (colon), and HL-60 (leukemia). Compounds displayed cytotoxic activity with IC50 values ranging from 0.19 to 8.96 µM. The anti-inflammatory activity of withajardins was evaluated by quantifying the release of nitric oxide (NO) induced by lipopolysaccharide (LPS) and the pro-inflammatory cytokines TNF-α and IL-6, in RAW 264,7 cells. The withajardins showed IC50 values from 74.43 to 354.40 µM in RAW 264.7 cells. In addition, attenuated the release of NO induced by LPS, and decreased the pro-inflammatory cytokines TNF-α and IL-6. Moreover, for some of the withanolides, molecular docking and dynamics studies against the new coronavírus (SARS-CoV-2) were carried out. The binding free energy results suggested that withanolides can be natural candidates against COVID-19 disease.